The Teaching Ministry of the Church An Examination of the Basic Prinicples of Christian Education - Smart, James D. (James Dick) (Philadelphia The Westminster Press, 1954)
In this valuable philosophy of Christian education for theologians, James Smart offers an excellent evaluation and redefinition of the goals of teaching ministry. Important topics addressed in this book include how to use the Bible in curriculum development and the relationship of the church to "secular"...
Keywords: Christian Education; Religious education